2023
DOI: 10.1002/batt.202300026
|View full text |Cite
|
Sign up to set email alerts
|

High Active Material Loading in Organic Electrodes Enabled by an in‐situ Electropolymerized π‐Conjugated Tetrakis (4‐Aminophenyl) Porphyrin

Abstract: Porphyrin complexes have been widely studied as promising electrode material in diverse energy storage systems and chemistries. However, like other organic electrodes, porphyrins often suffer from low conductivity and, consequently, require a significant amount (typically 40 %) of electrochemically inactive conductive carbon that occupies volume and mass without storing energy. In this study, we investigate [5,10,15,20 tetrakis(4‐aminophenyl)‐porphyrin] (TAPP) and its metal complexes as redox‐active cathode ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
2
2
Order By: Relevance
“…The altered structure of CuTPyP−MOF, in comparison to H 2 TPyP (Figure S24), results in a large contribution from diffusion‐controlled reaction, indicating a more battery‐like material character. This stands in contrast to previous studies, which showed dominant surface reactions upon the introduction of a copper ion [25a,29,41a] . Interestingly, the stronger faradaic character of CuTPyP−MOF does not influence the rate capability.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The altered structure of CuTPyP−MOF, in comparison to H 2 TPyP (Figure S24), results in a large contribution from diffusion‐controlled reaction, indicating a more battery‐like material character. This stands in contrast to previous studies, which showed dominant surface reactions upon the introduction of a copper ion [25a,29,41a] . Interestingly, the stronger faradaic character of CuTPyP−MOF does not influence the rate capability.…”
Section: Resultscontrasting
confidence: 99%
“…A comparative CV measurement (Figure S20) suggests that an additional redox peak, which occurs at 2.7 V in the anodic scan and reverses at 2.5 V in the cathodic scan, could be attributed to the copper atom in the porphyrin core structure. Previous research also reported on partial Cu(II) to Cu(I) redox reaction in Cu−porphyrins [25a,29,41a,42] . However, in this study, we observe the reaction to be more reversible and complete than previous studies have suggested.…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations